Association between composite dietary antioxidant index and fatty liver index among US adults - Zheng, Meng; Li, Chaochen; Fu, Jia; Bai, Long; Dong, Jinghui (Frontiers in Nutrition, 2024)
Background: The potential beneficial health effects of dietary antioxidants have been reported. However, the association of a composite dietary antioxidant index (CDAI) with fatty liver index (FLI) remains unclear. This study aims to assess whether CDAI (including its components) is associated with FLI among US adults. Methods: This population-based cross-sectional study used data on US adults from the National Health and Nutrition Examination Survey (NHANES) 2007-2018 cycles. Weighted generalized linear regression models were used to analyze the association between CDAI (including vitamin A, C, E, zinc, selenium, and carotenoids) and FLI, which was calculated by using body mass index (BMI), waist circumference and levels of γ-glutamyl transferase and triglycerides. Results: Weighted generalized linear regression models showed an inverse association between CDAI and FLI in the total population (β, -0.40; 95% CI, -0.59, -0.21), in women (β, -0.56; 95% CI, -0.94, -0.18), and in men (β, -0.32; 95% CI, -0.54, -0.10) after adjusting for various confounders. The restricted cubic splines showed the negative linear dose-response associations between CDAI and FLI (all P non_linear > 0.05). The dietary selenium intake in women has an inverse U-shaped relationship with FLI, with an inflection point value of 110 µg. In model 3, intake of dietary antioxidants Vitamins A, C, E, and carotenoids were significantly negatively associated with FLI in female but only were vitamins A and E negatively associated with FLI in male. In subgroup analysis, CDAI showed a significantly negative relation to FLI among those aged 60 years or older (β, -0.57; 95% CI, -0.81, -0.33), among those who engaged in active physical activity (β, -0.46; 95% CI, -0.63, -0.29), among those without metabolic syndrome (β, -0.43; 95% CI, -0.62, -0.24), and those without hyperuricemia (β, -0.43; 95% CI, -0.60, -0.26). Additionally, CDAI was significantly negatively associated with male FLI, regardless of whether they had diabetes or not. Conclusion: In conclusion, our results indicate that higher CDAI may be associated with a lower FLI.